Synthesis of hydroxyapatite from Labeo rohita fish scale for biomedical application. (2019) - Deb, Payel; Barua, Emon; Das Lala, Sumit; Deoghare, Ashish B.
Abstract: In the present research, hydroxyapatite (HAp) is derived from fish scales which are discarded as waste material. Scales of Labeo rohita fish has been calcined at 1000°C after acid treatment for HAp synthesis. The calcined powder is characterized using FTIR and XRD that confirms the formation of HAp. TGA shows the HAp is thermally stable between 800-900°C. SEM analysis reveals highly porous morphology of the derived HAp confirming its application in the development of bone scaffold. TEM analysis confirms the formation of polycrystalline micro HAp particles. The developed HAp can be a suitable biomaterial for orthopedic treatment.